2015
DOI: 10.1097/psy.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Microbiota in Acute Anorexia Nervosa and During Renourishment

Abstract: Objective The relevance of the microbe-gut-brain axis to psychopathology is of interest in anorexia nervosa (AN), as the intestinal microbiota plays a critical role in metabolic function and weight regulation. Methods We characterized the composition and diversity of the intestinal microbiota in AN, using stool samples collected at inpatient admission (T1) (n=16) and discharge (T2) (n=10). At T1, participants completed the Beck Depression and Anxiety Inventories and the Eating Disorder Examination-Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
226
4
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 250 publications
(250 citation statements)
references
References 84 publications
13
226
4
7
Order By: Relevance
“…Mixed evidence has emerged from investigations comparing the intestinal microbiotas of individuals with major depressive disorder to healthy controls, with one study failing to find significant between-group differences in microbial diversity or taxonomic composition [64], while the other found increased diversity and significant taxonomic differences at the phylum, family, and genus levels [11]. In patients with acute anorexia nervosa, which is frequently comorbid with depression, work from our laboratory has shown that microbial diversity was both associated with depression and significantly lower than in healthy controls [12]. Composition and diversity of the intestinal microbiota may also be associated with temperament in young children, but how such links may evolve during the development of adult personality is unclear [65].…”
Section: Discussionmentioning
confidence: 99%
“…Mixed evidence has emerged from investigations comparing the intestinal microbiotas of individuals with major depressive disorder to healthy controls, with one study failing to find significant between-group differences in microbial diversity or taxonomic composition [64], while the other found increased diversity and significant taxonomic differences at the phylum, family, and genus levels [11]. In patients with acute anorexia nervosa, which is frequently comorbid with depression, work from our laboratory has shown that microbial diversity was both associated with depression and significantly lower than in healthy controls [12]. Composition and diversity of the intestinal microbiota may also be associated with temperament in young children, but how such links may evolve during the development of adult personality is unclear [65].…”
Section: Discussionmentioning
confidence: 99%
“…One often proposed hypothesis is the varying degree to which certain microbes can extract calories from food, for example through the production of short-chain fatty acids (SCFAs) from indigestible carbohydrates (see below), resulting in an increased extraction of energy despite stable dietary intake [6]. Furthermore, studies have assigned a role for gut microbes in host metabolic rates, the latter of which was found altered in AN patients [3]. In this case, the resting energy metabolism decreased after FMT, possibly contributing to the gain in bodyweight.…”
mentioning
confidence: 99%
“…Fecal microbiota transplantation (FMT) from obese to nonobese subjects has led to weight gain despite unchanged dietary intake in animals as well as humans [2]. It has been repeatedly shown that short- and long-term dietary patterns including undernutrition and dieting in patients with AN can change the microbiota composition [3]. The notion that the gut microbiome can also affect nervous system functions through the gut-brain axis makes its involvement in eating behavior and psychiatric disorders plausible [4].…”
mentioning
confidence: 99%
“…Those peptides are often altered during the ill state of an eating disorder and normalize with recovery, but is it largely unknown whether they contribute mechanistically to AN [177]. A new area of research is the intestinal microbiome and one small study suggested that the bacterial composition in the intestine is altered in AN and that weight recovery is associated in changes in the microbiome [178]. Future research may identify pharmacological interventions that could be beneficial for the recovery from AN.…”
Section: New Approaches To Medication Intervention In Anmentioning
confidence: 99%